Difficulties Encountered in English Language Speaking Skills Among Second Language Learners (A Study Based on School Leavers at IPHS Campus, Akkaraipattu) - M. Ehiya Ahkam; M.J Fathima Sujani; M.R Rishad Muhammed; Singanayagam Umashankar (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This research explores into the Difficulties encountered in speaking English for second language school leavers at IPHS Campus, Akkaraipattu. The objective of the research were; to identify the difficulties encountered by school leavers when speaking English, to explore the factors and root causes of the difficulties, and the factors influences on their studies, to make them aware and understand by different and easy techniques to fulfill their studying target and objectives, to give them a proper guidance and good practice ways and to make them confident to overcome the struggles in their speaking skills. The research used a mixed method of qualitative and quantitate approach to collect data deeper in accordance. The first approach, questionnaire conducted to 24 students the rest of the instruments were implanted to 20 students. Using diverse research instruments, including questionnaires, practical tests, observations and interviews, the study categorizes difficulties into linguistic and non-linguistic domains. And the root causes are classified into educational, psycholinguistic, and environmental factors. The study not only conveys the difficulties but also provides suggestions and practical insights for learners and educators. A versatile approach involving appropriate curriculum adaptation, consistent practice, educator training, psychological support, family involvement, and technological integration is recommended. Implementing psychological support, like confidence-building workshops, and collaborating with families to emphasize language-based activities at home are crucial. In the digital age, integrating technology, such as language-learning apps and virtual exchange platforms, extends language exposure. These measures enhance the spoken English proficiency of second language school leavers, ensuring preparation for effective communication in diverse linguistic contexts. Techniques and suggestions derived from the analysis offer a comprehensive approach to develop effective spoken English skills among second language school leavers, contributing to the ongoing discussion on language education strategies.